2020
DOI: 10.1177/0020764020983860
|View full text |Cite
|
Sign up to set email alerts
|

Effects of brief training on mental health provider’s knowledge of working with youth at risk of suicide in Guatemala

Abstract: Background: Resources for mental healthcare are lacking in Guatemala, yet rates of mental illness and suicide are quite high. Mental healthcare providers often lack the knowledge needed to effectively work with young at-risk of suicide. To address this gap, we developed a training program for mental health professionals focused on increasing knowledge and understanding of engaging and working with youth at risk of suicide and present its acceptability and preliminary effectiveness. Methods: Mental health provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In addition, the ideological and political education of psychology in colleges and universities has formed a relatively complete teaching system after a long period of development. A large amount of data have also been accumulated in various stages such as school classroom teaching and students' after-school practice [33][34][35]. At the same time, every college and every student is generating massive amounts of data every day.…”
Section: E Development Process Of Public Mental Health Education In C...mentioning
confidence: 99%
“…In addition, the ideological and political education of psychology in colleges and universities has formed a relatively complete teaching system after a long period of development. A large amount of data have also been accumulated in various stages such as school classroom teaching and students' after-school practice [33][34][35]. At the same time, every college and every student is generating massive amounts of data every day.…”
Section: E Development Process Of Public Mental Health Education In C...mentioning
confidence: 99%
“…Regarding the studies that measured knowledge in suicide ideation and attempts for gatekeepers, results show an increase of knowledge at posttest in all the studies (Alonzo et al, 2020, 2021; Arenas-Monreal et al, 2021; Piedrahita et al, 2012; Pérez-Reyna et al, 2008). Within-group effect sizes were calculated for two studies that reported the raw data to conduct the computation (Alonzo et al, 2020, 2021). Large effect sizes were detected in the study training parents and teachers ( d = 1.25, 95% CI [0.58–1.86]; Alonzo et al, 2021) and medium effect sizes for the study training mental health providers ( d = 0.45, [−0.22, 1.13]; Alonzo et al, 2021).…”
Section: Resultsmentioning
confidence: 94%
“…Knowledge. Four studies include as a primary outcome the increase in knowledge about suicide ideation and attempts implemented for adolescents (Arias-Gutiérrez et al, 2009;Cañón et al, 2018;Chávez-Hernández et al, 2008;Figueredo, 2020) and five studies measure the increase in knowledge for gatekeepers (Alonzo et al, 2020(Alonzo et al, , 2021Arenas-Monreal et al, 2021;Piedrahita et al, 2012;Pérez-Reyna et al, 2008).…”
Section: Intervention Effectsmentioning
confidence: 99%
See 2 more Smart Citations